The relationship between the three-factor eating questionnaire (TFEQ) subscales (dietary restraint, disinhibition, and hunger) and the body mass index: A cross-sectional study among female students - Nujud Almuhammadi; Waad Alfawaz (Heliyon)
Background: Identification of an individuals vulnerability to specific eating behaviours could explain weight variations, which could help develop tailored interventional programs to prevent obesity and other pathological eating behaviours. However, there is no baseline data available on the associations between the subscales of the Three-Factor Eating Questionnaire (TFEQ) (dietary restraint, disinhibition, and susceptibility to hunger) and the body mass index (BMI) in a sample of the Saudi population. Thus, this study examines the relationship between the BMI and eating behaviours of Saudi female students, using the scores of the TFEQ subscales. Methods: This cross-sectional study was conducted at King Saud University (KSU) with 200 female students who completed the Arabic version of TFEQ. The mean age of the participants was 22.88 ± 3.60 years. A Pearson correlation test determined the association between the TFEQ subscales and the BMI. Results: More than 50 % of the participants had a mean BMI of 23.57 ± 5.15 kg/m2 and a majority showed medium-to-high restraint scores (n = 150). Moreover, 70 % (n = 140) of the particpants showed significantly low disinhibition traits, and a significant positive correlation between BMI and eating behaviour (P ≤ 0.05). Among all TEFQ subscales, disinhibition significantly correlated with the BMI (r = 0.38, P < 0.000) the most, followed by dietary restraint (r = 0.18, P < 0.007). In contrast, susceptibility to hunger was the least associated with the BMI (r = 15, P < 0.029). Conclusions: The study indicated that all TFEQ subscales play an important role in weight variability, increasing the risk of eating disorders among college-aged Saudi female students. The BMI positively correlated to the students' eating behavioural profiles of high restrain, high disinhibition, and high hunger, and the hidden risk for eating disorders and obesity in normal-weight female students was high. Thus, interventional programs directed at Saudi female students, based on the eating behaviour traits that affect their BMIs, are recommended for managing weight and preventing eating disorder pathologies.